The embrace of the Holy Apostles Peter and Paul:: history and iconography (Philology, 2019)
The iconographic type, “The Embrace of the Holy Apostles Peter and Paul”, together with its variations, was chosen as the starting point for the history of the two Leaders of the Apostles Peter and Paul. A nucleus around “The Embrace” is drawn in the study, the traces of which link up the miraculous icon from the Monastery of Karakallou to works of icon-painters from the 15th-century Cretan School, and to an early icon from the Monastery of Vatopedi on Mount Athos from 1160 – with similar images, typical of churches in Sicily at the same time. The roots of this iconographic type are sought in two directions – in New Testament texts and hagiographic literature (the specifics of the topic also require usage of some apocryphal texts), but also in early images in the Roman catacombs.
Keywords: The Holy Apostles Peter and Paul; “The Embrace”; iconography; hagiographic literature; apocryphal texts